Pola Adaptasi Lingkungan Penghuni Dolina Kidang pada Masa Prasejarah di Kabupaten Blora - Indah Asikin Nurani (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2022)
Dolina Kidang is a funnel-shaped cavity on the ground surface connected to the underground canal system in limestone areas. In this Dolina, there are two caves facing each other. Based on the results of a cave survey of in Blora Regency, Dolina Kidang is the only residential cave that has archaeological potential. This fact is an interesting problem to study, why is there a prehistoric cave dwelling in the Blora Regency area? How is it related to the distribution of prehistoric cave dwellings in Gunung Sewu, this area should have great potential. Blora Regency is an important area with archaeological remains from the Pleistocene, such as the Ngandong, Jigar, and Sungun sites in the Bengawan Solo watershed. This paper is intended to explain the cultural importance of prehistoric cave dwellings in the Rembang Zone. In addition, this study will also examine how the pattern of human adaptation and roaming to survive with the availability of natural resources around it. The method used is descriptive-explanatory based on the findings of the excavation which is then linked to the spatial aspect. Based on the results of these analyzes and observations, it can be understood how the humans who inhabit the Kidang Dolina adapt to the surrounding environment, especially in applying the pattern of the hunting season for animals (for consumption), the use of bone and shell remains and sources of rock materials to make tools.